The Influence of Training and Development Programs, Job Autonomy, and Organizational Culture on Employee Job Satisfaction and Performance - Soegiarto, Ita; Sihite, Mislan; Usmany, Paul (International Journal of Business, Law, and Education, 2024)
This research explores the intricate relationships between training and development programs, job autonomy, organizational culture, and employee outcomes, with a specific focus on the mediating role of job satisfaction. The study employs a mixed-methods approach, integrating quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) with qualitative insights gathered from interviews and focus group discussions. The results highlight the positive impact of effective training programs, job autonomy, and a supportive organizational culture on job satisfaction levels among employees. Job satisfaction emerges as a crucial mediator, translating these organizational factors into improved performance, motivation, and overall well-being. The findings underscore the importance of prioritizing strategies that enhance job satisfaction to foster a more engaged and productive workforce, ultimately contributing to organizational success